Kyrgyz Republic : Kyrgyz Republic-Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Kyrgyz Republic's Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility. Following exceptionally strong performance in 2013, growth is moderating to a more sustainable pace. The program is broadly on track, with all end-December 2013 quantitative performance criteria and all but one indicative targets (IT) met for end-December 2013. Although three March 2014 ITs were missed, since then there has been progress in rebuilding reserves and enhancing tax collections. The two structural benchmarks for end-December were met. The IMF staff supports the completion of the sixth and final review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet